METHODS OF DEVELOPING DIDACTIC GAMES IN PRESCHOOL EDUCATION ORGANIZATIONS AND THEIR PEDAGOGICAL EFFECTIVENESS - DJumayeva Zarnigor Aloxiddinova qizi (International Journal of Literature and Language Studies, 2026)
This article systematically investigates the scientific-theoretical foundations, modern methodical approaches, and pedagogical effectiveness of developing didactic games in preschool education organizations. Nowadays, the excessive academization of the educational process and the alienation from game technologies, which constitute the leading activity of preschool children, are analyzed as a pressing pedagogical contradiction. Within the framework of the study, traditional educational methods (frontal explanation and demonstration) were compared experimentally with the author's developed